RISC-V Based Hardware Acceleration of Interval Contractor Primitives in the Context of Mobile Robotics - Pierre Filiol; Bollengier, Theotime; Jaulin, Luc; Le Lann, Jean-Christophe (Acta cybernetica (Szeged), 2024)
Localization tasks, generally modeled as Constraint Satisfaction Problem (CSP), are recurring problems in mobile robotics. Known approaches rely on software libraries which all have their advantages but also their limitations, among which non-optimal computing performances. This paper proposes a different approach which consists in extending the RISC-V ISA to provide hardware support for interval primitives.